Effect of Acid-Based Level on Storage Acrylic Emulsion Paint - Hutapea, Henny; Sembiring, Yulia Shara; Setna, Nathanael (Indonesian Scholar Society, 2022)
In the present study, a novel methodology was developed for the assessment of acid-based effect levels on the storage acrylic emulsion paints., It was found that the acrylic emulsion paint was clumping and smelled bad on the organoleptic test. Most bacterial growth on the microbiological test. This occurred in the acrylic emulsion paint sample which had a pH level of 7. Microbiological checking found little bacterial growth in the paint which had a level of pH 9, which is relatively safe in the storage process for 30 days and has good results in organoleptic and microbiological tests.